Positive Emotions at Work and Job Crafting: Results From Two Prospective Studies - Rogala, Anna; Cieslak, Roman (Frontiers in Psychology, 2019)
To date, research confirmed the effects of job crafting on the functioning of employees and organizations. In contrast, the evidence for the predictors of job crafting is limited. Based on Broaden–and–Build Theory it may be assumed that high positive emotions at work would predict high job crafting behaviors at follow-ups. In line with Social Cognitive Theory, it may be hypothesized that self-efficacy would mediate the relationship between positive emotions at work and following job crafting behaviors. The hypotheses were tested in a three-wave prospective study (Study 1, N = 124), with individual beliefs measured as the predictors. In a three-wave prospective Study 2 (N = 99), individual perceptions of collective flow at work and collective efficacy were assessed. Results of Study 1 and 2 indicated that positive emotions at work predicted increasing structural resources, a job crafting dimension. Moreover, findings of Study 2 showed that collective flow at work predicted another job crafting dimension, i.e. increasing social resources. These results may inform good practices and help in designing individual- and team-level interventions enhancing job crafting behaviors.